Mechanochemical synthesis of phthalimides with crystal structures of intermediates and products1. Issue 12 (28th March 2015) - Colaço, Melwin; Dubois, Jean; Wouters, Johan
<x xml:space="preserve">Abstract</x> Phthalimides have been successfully synthesized in the solid state by grinding (or kneading) of substituted phthalic anhydride and aniline derivatives. Selected products and intermediates were crystallized and characterized by crystallography leading to a potential rationale for the solid-state reactivity that involves co-crystals as intermediates.